Analysis of the sense of integration of youth of Maghrebi origin in Catalonia through the decision trees technique - Vilà Baños, Ruth; Palou Julián, Berta; Rubio Hurtado, María José (Pulso. Revista de educación, 2019)
This article presents the application of decision trees, a data mining analysis technique, in a study evaluating the factors influencing the sense of integration of youth, where integration is addressed from an intercultural approach of dialogue and exchange in a dynamic and multidimensional process. In this study, we try to identify the key elements regarding intercultural coexistence to make young people of Maghrebi origin feel integrated into the Catalan society. For the analysis, The Social Cohesion among Young People questionnaire was applied to a sample of 3498 young people of 47 secondary education centers belonging to 37 municipalities of Catalonia. The results indicate that the youth of Maghrebi origin has a higher percentage of sense of non-integration compared to the rest of young people. The key elements regarding the intercultural coexistence to feel integrated are the cultural origin of their friends in the educational center and the time of residence in Catalonia.